Postpartum Management After Obstetric Anal Sphincter Injuries. Issue 4 (October 2017) - Eubanks, Allison; Petersen, Scott M.
Abstract : A 26-year-old woman, gravida 1 para 1, experiences a severe perineal laceration that extends through the rectal mucosa after a vaginal delivery. She asks you, "What can be done to optimize my recovery?" Abstract : Limited information is available for the optimal postpartum treatment of women with obstetric anal sphincter injuries.